Sculpting foraminifera - Maric, Filip; Poto, Margherita; Zimmermann, Heike Jane; Panieri, Giuliana (Septentrio Educational, 2023)
Focus:To appreciate the biodiversity of the Arctic Ocean and ocean floor, with a particular focus on lesser-known species like foraminifera.Learning objectives:In this activity, pupils will identify (one, two, or several) foraminifera species living at or close to the Arctic Ocean floor and sculpt them using modelling clay.Key words:Foraminifera, Benthic, Planktonic.